If it's not what You are looking for type in the equation solver your own equation and let us solve it.
13-5k=5k+3
We move all terms to the left:
13-5k-(5k+3)=0
We get rid of parentheses
-5k-5k-3+13=0
We add all the numbers together, and all the variables
-10k+10=0
We move all terms containing k to the left, all other terms to the right
-10k=-10
k=-10/-10
k=1
| (x+4)^2-2x-5=(x-1)^2 | | 2(x+2)+3x=2(x+1+1 | | 9g-7g+2g+2g-g=5 | | b^2+2b=−20 | | b2+2b=−20 | | -2x+2-7x=-46-15x | | 5a+10-3a-12=6 | | 6x+11=-2x+1 | | 24x-7=4-42x | | 19=n | | 12x-(2x-9)=29 | | –3=5k+7 | | -24x-7=-3-56x | | (21+9)–(8–4)=p | | -4x+2-3x=42-15x | | 7(x+1)+3=3x+4(x+2+2 | | 0.6x-5=7+0.1 | | 18-1/6x=1/6x+6 | | -2v=40+3v | | b/9-3=-2 | | 1/4x^2-5/2x+6=0 | | 6k+2=77-9 | | n/15=6/9 | | 10=m+11 | | x^2/4-5/2x+6=0 | | 3c-10=3c-9 | | 78+8x=-5 | | 12y-11y=20 | | 4(x-3)=8(x-2)4x | | 1.5y-12=-6 | | 14)3(x-7)=48 | | -2(p-4)-9p=-25 |